Investigation on the Effects of Different Concentration of CO2 Gas Injected into Fresh Cement Paste Along with the Addition of Superplasticizer on the Mechanical Properties of Cement - Soesilo, Egy Crystal; Putera, Muhammad Akmal; Daryono, Lutfian Rusdi; Abe, Tomohiko (Himpunan Ahli Teknik Tanah Indonesia, 2024)
This paper focused on examining the impact of injecting varying concentrations of carbon dioxide (CO2) gas on the mechanical characteristics of both the fresh and hardened states of cement paste. This study also considered the influence of the presence or absence of polycarboxylate superplasticizer in cement mixture on these properties. Many researchers discovered the benefit of CO2 gas utilization in cement mixture to accelerate the early strength of cement or concrete hydration by its carbonation that form calcium carbonate (CaCO3). The application method is to directly inject CO2 gas in a curing chamber for air-curing of precast concrete. Alternatively, carbonated water is mixed with cement during concrete mixing. However, the use of CO2 gas does not significantly improve the 28-day strength of concrete. This study explores how to improve the carbonation impact on mechanical properties of cement paste and apply it to ground improvement. In this study, the method adopted is direct injection of CO2 gas during cement slurry mixing with different injection duration. The influence of CO2 in the presence of superplasticizer (SP) in cement slurry was also studied as SP is generally used for grouting. The results showed that the carbonation of cement paste with additional of superplasticizer significantly affect its flow, viscosity and bleeding properties. Unlike samples with SP addition, the samples without SP addition showed higher compressive strength after 28 days of curing up to certain CO2 injection time. For all CO2 gas injection time, smaller porosity rates were observed for 7-day cured samples with SP addition compared to those without SP addition. This is due to accelerated carbonation due to SP presence in cement mixture. From the results, the optimum of CO2 gas injection time for one liter mixture of cement paste to improve its compressive strength (up to 123% increase) have been discovered. It can be inferred that the addition of superplasticizer in cement slurry reduces the amount of CO32- ions and Ca2+ ions during carbonation process of cement hydration products, which are strongly related to the pH level in pore solution. These ions play a significant roles in determining the mechanical properties of cement slurry.